2018
DOI: 10.1084/jem.20171576
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol negatively regulates IL-9–producing CD8+ T cell differentiation and antitumor activity

Abstract: CD8+ T cells can be polarized into IL-9–secreting (Tc9) cells. Ma et al. show that Tc9 cell differentiation is associated with a low cholesterol reprogramming profile, and manipulating cholesterol content in polarizing Tc9 cells significantly affects Tc9 differentiation and antitumor response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
103
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 54 publications
1
103
1
2
Order By: Relevance
“…Type 9 cells have been shown to persist long term in vivo after transfer in multiple studies (Lu et al, 2012, 2014; Ramadan et al, 2017). Ma et al (2018) show here that Tc9 cells from Pmel-1 mice, a transgenic strain that carries a rearranged T cell receptor specific for pmel-17, an orthologue of the melanocyte differentiation antigen gp100, which is overexpressed in many human melanomas, persist longer than Tc1 cells when adoptively transferred into MC38-gp100 tumor bearing mice. Treatment of Tc9 cells with β-CD before adoptive transfer increased their persistence in vivo, whereas treatment with cholesterol decreased their persistence compared with untreated Tc9 cells by decreasing and increasing apoptosis, respectively.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Type 9 cells have been shown to persist long term in vivo after transfer in multiple studies (Lu et al, 2012, 2014; Ramadan et al, 2017). Ma et al (2018) show here that Tc9 cells from Pmel-1 mice, a transgenic strain that carries a rearranged T cell receptor specific for pmel-17, an orthologue of the melanocyte differentiation antigen gp100, which is overexpressed in many human melanomas, persist longer than Tc1 cells when adoptively transferred into MC38-gp100 tumor bearing mice. Treatment of Tc9 cells with β-CD before adoptive transfer increased their persistence in vivo, whereas treatment with cholesterol decreased their persistence compared with untreated Tc9 cells by decreasing and increasing apoptosis, respectively.…”
mentioning
confidence: 82%
“…In T cells, cholesterol can influence TCR signaling, immunological synapse formation, and cytokine secretion, all of which can influence antitumor activity (Wang et al, 2016; Yang et al, 2016). To identify cholesterol as a negative regulator of Tc9 differentiation, Ma et al (2018) first used Ingenuity Pathway Analysis comparing microarrays from murine cytotoxic CD8 T cells differentiated under type 1 (IL-2 and IL-12) and type 9 (TGF-β and IL-4) cytokine conditions. They found that Tc9 cells have lower basal expression of cholesterol synthesis genes, such as Hmgcr and Sqle , and high expression of cholesterol efflux genes, such as Abca1 and Abcg1 , than Tc1 cells.…”
mentioning
confidence: 99%
See 3 more Smart Citations